PENGARUH PEMBERIAN AKUPRESURE TERHADAP KECEMASAN PADA REMAJA DISMENORHEA - Tentya Indah Masfufa; Nurul Hidayah; Diah Ayu Dwi Satiti; Oktaviana Thresia Monika Barbara Adam (Ensiklopedia of Journal, 2025)
Abstract: Dysmenorrhea is pain experienced by adolescents during menstruation. Dysmenorrhea is caused by an imbalance of the hormone progesterone in the blood, prostaglandins and stress/psychological factors resulting in the occurrence of dysmenorrhea in some women. Anxiety is an unpleasant feeling that is described by restlessness or tension and abnormal hemodynamic signs as a consequence of sympathetic, parasympathetic and endocrine stimulation. One of the non-pharmacological therapies is by emphasizing the P6 meridian point.. The purpose of this study was to determine the effect of acupressure on anxiety in dysmenorrheal adolescents. The type of research used is experimental, namely pre-experimental with a one group pre-post test design. The sample in this study were 18 students who experienced dysmenorrhea. Measurement of anxiety using the STAI questionnaire (Y). The results showed that the average level of anxiety before being given acupressure was 2.28, then given acupressure, it showed that there was a change in the average level of anxiety, which was 1.28. From the results of statistical tests with the Wilcoxon test, the p value value is 0.000. It can be said that the administration of acupressure is effective or has a good influence on reducing anxiety in dysmenorrheal adolescents. Giving acupressure during dysmenorrhea is very useful in overcoming anxiety problems in adolescents. It is recommended that health workers can provide knowledge about acupressure in overcoming anxiety problems during dysmenorrhea.Keywords: Acupressure, Anxiety, Adolescent.